Antigenic and Genetic Characterization of Swine Influenza Viruses Identified in the European Region of Russia, 2014–2020 - Danilenko, Daria M.; Komissarov, Andrey B.; Fadeev, Artem V.; Bakaev, Mikhail I.; Ivanova, Anna A.; Petrova, Polina A.; Vassilieva, Anastasia D.; Komissarova, Kseniya S.; Zheltukhina, Alyona I.; Konovalova, Nadezhda I.; Vasin, Andrey V. (Frontiers in Microbiology, 2021)
Pigs have long been recognized as "mixing vessels" in which new viruses are formed by reassortment involving various influenza virus lineages (avian, animal, human). However, surveillance of swine influenza viruses only gained real significance after the 2009 pandemic. A fundamentally important point is the fact that there is still no regular surveillance of swine flu in Russia, and the role of swine viruses is underestimated since, as a rule, they do not cause serious disease in animals. Since the pig population in Russia is large, it is obvious that the lack of monitoring and insufficient study of swine influenza evolution constitutes a gap in animal influenza surveillance, not only for Russia, but globally. A six-year joint effort enabled identification of SIV subtypes that circulate in the pig population of Russia's European geographic region. The swine influenza viruses isolated were antigenically and genetically diverse. Some were similar to human influenza viruses of A(H1N1)pdm09 and A(H3N2) subtype, while others were reassortant A(H1pdm09N2) and A(H1avN2)) and were antigenically distinct from human H1N1 and H1N1pdm09 strains. Analysis of swine serum samples collected throughout the seasons showed that the number of sera positive for influenza viruses has increased in recent years. This indicates that swine populations are highly susceptible to infection with human influenza viruses. It also stresses the need for regular SIV surveillance, monitoring of viral evolution, and strengthening of pandemic preparedness.